Cholesterol, high-density lipoprotein, and glucose index versus triglyceride–glucose index in predicting cardiovascular disease risk: a cohort study - Degang Mo; Peng Zhang; Miao Zhang; Hongyan Dai; Jun Guan (Cardiovascular Diabetology)
Abstract Background Cardiovascular disease (CVD) represents a significant global health challenge, characterized by high incidence rates and substantial morbidity and mortality. A newer index, the Cholesterol, High-Density Lipoprotein, and Glucose (CHG) index, has been proposed as a potential diagnostic tool for metabolic disorders but has not been investigated for its ability to predict CVD risk. This study aims to evaluate the predictive efficacy of the CHG index in comparison to the well-established Triglyceride–Glucose (TyG) index. Methods In this cohort study, 6249 adults aged 45 and older were recruited from the CHARLS database, with data collected from 2011 to 2020. CVD events were tracked over a nine-year follow-up. The TyG and CHG indices were calculated, and their relationships with CVD risk were assessed using univariate and multivariate Cox regression models. Additionally, restricted cubic spline (RCS) analysis was performed to further explore these associations. Receiver operating characteristic (ROC) analysis was conducted to compare the predictive performance of both indices, and subgroup analysis evaluated their applicability in different populations. Results Among the 6249 participants, 1667 (26.68%) developed CVD during the nine-year follow-up. In unadjusted Cox regression models, the TyG index had a hazard ratio (HR) of 1.18 (95% confidence interval CI 1.10–1.27, p < 0.001), while the CHG index showed a higher HR of 1.35 (95% CI 1.21–1.51, p < 0.001). In the adjusted models, the relationship still persisted. The RCS models showed that the TyG index exhibited a non-linear relationship with the risk of CVD, while the CHG index demonstrated a positive linear correlation. ROC curve analysis revealed comparable predictive performance for both indices. The subgroup analysis indicated that there was no interaction between the subgroups and the both indices (p for interaction > 0.05). Conclusions An elevated CHG index is significantly correlated with an increased risk of CVD, demonstrating a linear relationship. Furthermore, it exhibits predictive capabilities comparable to those of the TyG index in assessing CVD risk. Trial registration Not applicable. Graphical abstract